2019
DOI: 10.13005/bpj/1635
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Cyclophosphamide Induced Immunosupression by the Hydro-Alcoholic Extract of Gymnema Sylvestre Leaves in Albino Rats

Abstract: Cyclophosphamide (CP), the most commonly used anti-neoplastic agent causes immunosuppression and toxic effects on various organs that are the limiting factors of cancer treatment. It can be hypothesized that addition of new immunopotentiating agents with detoxification properties would have beneficial role in cancer therapy. Many researchers have proved that, if certain plant products are combined with cancer chemotherapeutic agents, reduce toxicities and improve tumour response. In Ayurveda, Gymnema sylvestre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Ethanol extract of this plant was observed to improve immunosuppressed condition induced by cyclophosphamide in Albino Rats. In this study, the plant extract significantly improved haemagglutination titer, phagocytic activity and decreased paw edema ( p < 0.01, p < 0.05 and p < 0.05 respectively), when compared with cyclophosphamide treated control (Kar et al, 2019). In another study, potent immunostimulatory potential of the aqueous extract of this plant was observed (Gupta et al, 2009).…”
Section: In Vitro and In Vivo Pharmacological Activity Reports On Gymmentioning
confidence: 57%
“…Ethanol extract of this plant was observed to improve immunosuppressed condition induced by cyclophosphamide in Albino Rats. In this study, the plant extract significantly improved haemagglutination titer, phagocytic activity and decreased paw edema ( p < 0.01, p < 0.05 and p < 0.05 respectively), when compared with cyclophosphamide treated control (Kar et al, 2019). In another study, potent immunostimulatory potential of the aqueous extract of this plant was observed (Gupta et al, 2009).…”
Section: In Vitro and In Vivo Pharmacological Activity Reports On Gymmentioning
confidence: 57%
“…It has been used successfully in refractive cases. As a hyperimmune globulin, it functions to neutralize virus particles and reduces viremia and mortality rates by up to 30–40% [ 57 , 77 , 89 ]. Antibodies are collected from the plasma of smallpox-immune individuals to create passive immunity.…”
Section: Resultsmentioning
confidence: 99%
“…Knowing the scope of current targeted therapy approaches such as those based on microRNAs and silencing RNAs, there is work happening to find accurate targeted molecules against mpox [ 3 , 74 ]. Similarly, biomarker-based therapies are also in research annals as biomarkers offer an effective targeting and flexible drug design approach against different kind of diseases [ 89 ]. For viral diseases, the biobased approaches allow effective screening, diagnosis, prognosis, and mitigative vaccination and adaptive treatment measures [ 80 , 98 ].…”
Section: Resultsmentioning
confidence: 99%